2018
DOI: 10.1007/s00018-018-2832-x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of hippocampal progenitors relies on p27-dependent regulation of Cdk6 kinase activity

Abstract: Neural stem cells give rise to granule dentate neurons throughout life in the hippocampus. Upon activation, these stem cells generate fast proliferating progenitors that complete several rounds of divisions before differentiating into neurons. Although the mechanisms regulating the activation of stem cells have been intensively studied, little attention has been given so far to the intrinsic machinery allowing the expansion of the progenitor pool. The cell cycle protein Cdk6 positively regulates the proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Loss of CDK6 specifically prevents the expansion of neuronally committed precursors by lengthening G 1 phase duration and premature CC exit, resulting in decreased neurogenesis (Beukelaers et al, 2011). The group of Caron et al (2018) then asked for the mechanism of CDK action in adult SGZ precursors. By generating mice bearing a kinase-dead allele of CDK6 they demonstrated that the function of CDK6 in hippocampal neurogenesis relies essentially on its kinase activity.…”
Section: Specific Roles Of Cell Cycle Components In Regulating Adult mentioning
confidence: 99%
“…Loss of CDK6 specifically prevents the expansion of neuronally committed precursors by lengthening G 1 phase duration and premature CC exit, resulting in decreased neurogenesis (Beukelaers et al, 2011). The group of Caron et al (2018) then asked for the mechanism of CDK action in adult SGZ precursors. By generating mice bearing a kinase-dead allele of CDK6 they demonstrated that the function of CDK6 in hippocampal neurogenesis relies essentially on its kinase activity.…”
Section: Specific Roles Of Cell Cycle Components In Regulating Adult mentioning
confidence: 99%
“…The demonstrated involvement of CDKs in proinflammatory gene expression makes these proteins promising target for treatment of chronic inflammatory diseases. CDK6 has been implicated in the proliferation, differentiation, and survival of neurons (Beukelaers et al, 2011; Mi et al, 2013; Caron et al, 2018; Hasenpusch-Theil et al, 2018). For example, preventing CDK6 over-activation can reduce 6-hydroxy-dopamine-induced neuronal death (Alquezar et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…During hippocampal neurogenesis, the proliferation of progenitor cells specifically relies on the p27-dependent regulation of MCPH12 kinase activity. CDK2, CDK4, and cyclin D1 were downregulated, whereas p21 (Waf1/Cip1) and p27 (Kip1) were upregulated in MCPH19 knockdown cells compared with in control cells [68]. The role of p27 in carcinogenesis was revealed through studies involving MCPH19 [82].…”
Section: Gene Neurogenesis Ref Carcinogenesismentioning
confidence: 99%
“…Regulating radial glial cells G1 and S phases [66] DNA damage response, apoptosis (epithelial ovarian cancer) [67] Positively regulates the proliferation of hippocampal progenitors [68] Cell cycle (glioblastoma) [69] Proliferation of neural stem cells [70] Cell cycle, cell proliferation and angiogenesis (hematopoietic malignancies) [71] Cell cycle and apoptosis (T-cell acute lymphoblastic leukemia) [72] MCPH13 (CENPE) N/A Cell G2/M phase and proliferation (lung cancer) [25] MCPH14 (SAS6) N/A Centrosome amplification, mitotic abnormality (CRCs) [73] MCPH15 (MFSD2A) Blood-brain barrier disruption [74] Cell cycle (G1 phase) and matrix attachment (lung cancer) [41] MCPH16 (ANKLE2) Reduced cell proliferation [75] N/A…”
Section: Mcph3 (Cdk5rap2)mentioning
confidence: 99%
See 1 more Smart Citation